Women Writing Intimate Spaces The Long Nineteenth Century at the Fringes of Europe - Lindh Estelle, Birgitta; Duțu, Carmen Beatrice; Parente-Čapková, Viola (Brill, 2022)
The messy and multi-layered issue of intimacy in connection with transnationality and spatiality is the topic of this volume on women's writing in the long nineteenth century. A series of intimacies are dealt with through case studies from a wide range of countries situated on the European fringes. Within the field of feminist literary studies, the volume thus differs from other publications with a narrower scope, such as Western Europe or specific regions. More broadly, the chapters in this volume offer a variety of approaches to intimacy and generous bibliographical references for researchers in humanities and cultural studies.